Evaluation of Brachypodium spp. System Model Against Fusarium poae - Florencia Arroyo; Mauro Martínez; Agustín Arata; María V. Moreno; Marie Dufresne; Sebastián A. Stenglein; María I. Dinolfo (Journal of Fungi)
Cereal crops are affected by one of the most devastating diseases worldwide, known as Fusarium head blight (FHB), with Fusarium graminearum being the most isolated causal pathogen. Another species associated with this disease is Fusarium poae. This species has been considered a relatively weak pathogen compared to F. graminearum, but its importance has increased due to its occurrence in cereal grains worldwide. Considering the advantages of using B. distachyon as a plant model and the importance of F. poae in crops, our study aimed to evaluate the potential use of Brachypodium as a plant model to evaluate the compatible interaction with F. poae. Twelve Brachypodium spp. accessions from different countries were inoculated with a selected F. poae set of isolates. Disease severity, conidial quantification, fungal DNA biomass, and nivalenol quantification were assessed. The results showed a compatible interaction between Brachypodium accessions and Fusarium poae, which allowed the use of the model plant for future plant–pathogen interaction studies.